2005
DOI: 10.1111/j.1365-2125.2004.02264.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and tolerability of different doses of fentanyl following sublingual administration of a rapidly dissolving tablet to cancer patients: a new approach to treatment of incident pain

Abstract: AimsIt is estimated that two-thirds of cancer patients will at some point during their illness experience breakthrough pain. In this study, the pharmacokinetics of a novel sublingual dosage form of fentanyl developed for breakthrough pain was evaluated. MethodsEleven Caucasian patients (seven male and 4 female, aged 34-75 years, median 60 years) with metastatic malignant disease were recruited initially, but three patients withdrew. Prior to the study all patients were on continuous nonfentanyl opiate medicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(49 citation statements)
references
References 18 publications
3
41
1
4
Order By: Relevance
“…This finding confirms pharmacokinetics studies in which a detectable plasma concentration of fentanyl occurred in 8-11 minutes 21 . A reduction of approximately two points or a reduction of approximately 30% of pain intensity has been reported to be a cut-off for clinically important difference 29 .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This finding confirms pharmacokinetics studies in which a detectable plasma concentration of fentanyl occurred in 8-11 minutes 21 . A reduction of approximately two points or a reduction of approximately 30% of pain intensity has been reported to be a cut-off for clinically important difference 29 .…”
Section: Discussionsupporting
confidence: 80%
“…Sublingual fentanyl (SLF) is a second generation ROO, formulated as a rapidly disintegrating tablet system containing a mixture of carrier particles coated with active drug particles and containing a mucoadhesive agent. The bioavailability of SLF is estimated to be about 70% 20 , with an interindividual variability lower than that reported with oral transmucosal fentanyl 21 . Controlled studies have demonstrated the efficacy and safety of SLF for the management of BTP 22,23 .…”
Section: Introductionmentioning
confidence: 96%
“…However, further work with this approach is needed before widespread use. Other studies involving sublingual sufentanil and fentanyl [36][37][38] also suggest a very rapid onset of these lipid-soluble opioids.…”
Section: (Continued)mentioning
confidence: 93%
“…With fentanyl sublingual tablets (FST), the first trace of fentanyl in the blood can be demonstrated 8 to 10 minutes after administration; the maximum concentration is seen in a dose-dependent manner after 40 to 58 minutes (16). The bioavailability has not yet been investigated in studies; it is estimated at 70% (17).…”
Section: Fentanyl Sublingual Tabletsmentioning
confidence: 99%